Efektivitas Konseling Kelompok Dalam Meningkatkan Pengelolaan Emosi Warga Binaan di UPTD – RAMPK- Ogan Ilir - Yeni Anna Appulembang; Angeline Hosana Zefany Tarigan; Indra Prapto Nugroho; Rifda Alda Ufaira (Altifani Journal: International Journal of Community Engagement, 2026)
The emergence of Social Welfare Problem Bearers (PMKS) indicates that society is facing complex issues. Therefore, the government provides rehabilitation programs in various regions, one of which is at the Special Protection Rehabilitation Social Institution for Children located in Ogan Ilir, South Sumatra. The institution currently accommodates 27 residents. For three months, the residents received hard skill training. However, based on observations, some residents still experience difficulties originating from themselves, such as self-control and difficulty in managing anger. Therefore, the team provided an intervention in the form of group counseling. The activities consist of three stages: (1) pretest, (2) counseling, and (3) posttest. The counseling session itself consists of five stages: (a) initial stage, (b) transition stage, (c) working stage, (d) termination stage, and (e) follow-up stage. Based on statistical data analysis using a paired sample t-test, it was found that there is a difference in scores before and after group counseling. This indicates that there is a change before and after group counseling.